Correlation Between Knowledge Level About Cloth Sanitary Napkins and Interest in Using Cloth Sanitary Napkins for Young Women - Imbuh Nur Leni; Retno Heru Setyorini; Teguh Budi Prasetya; Pri Hastuti (CV. Rayyan Dwi Bharata, 2023)
Long-term use of disposable sanitary napkins can cause reproductive health problems and have an impact on the environment. In the modern era, rewashable cloth pads appeared. Based on the data obtained on young women aged 12-15 years, it was found that 23 young women were still using disposable pads. 82.6% of young women did not know what cloth sanitary napkins were and how useful they were, while 17.4% of young women already knew what cloth sanitary napkins were and did not know the benefits of cloth sanitary napkins. Knowledge about the use of cloth sanitary napkins is still low regarding management in dealing with menstruation which in turn impacts on the use of inappropriate sanitary napkins. This study aims to determine the relationship between the level of knowledge about cloth sanitary napkins and interest in the use of cloth sanitary napkins for young women at SMP Negeri 2 Sewon, Bantul Yogyakarta. This type of research is quantitative with a survey method and a cross sectional research design. The population of this study were eighth grade girls at SMP Negeri 2 Sewon. A sample of 57 young women. The sampling technique in this study was using proportional stratified random sampling. Data collection was carried out using a data questionnaire using univariate and bivariate analysis. The results showed that the level of knowledge about cloth sanitary napkins which was lacking was 4 people (7%), 7 people (12.3%) were sufficient, and good were 46 people (80.7%) and interest in using cloth sanitary napkins for young women with the category low interest amounted to 9 people (15.8%), moderate interest 42 people (73.7%), high interest 6 people (10.6%). The results of the bivariate analysis obtained a p value of 0.009 so that the p value 0.05. The conclusion of this study is that young women have a good level of knowledge and have a moderate interest in using cloth sanitary napkins and there is a relationship between the level of knowledge and interest in using cloth sanitary napkins.